Juridical Analysis of Standard Procedures for Implementing Referrals in Community Health Centers with Limited Health Personnel - Santoso, Aris Prio Agus; Nugrahanti, Joyce Hestia; Susilowati, Tri; Sunaryanti, Betty (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The current condition of health workers utilized in Indonesian Community Health Centers still experiences inequality in number and distribution. Limited human resources for health are an obstacle in realizing sustainable health development. The aim of this research is to find out what the Standard Procedures for Referrals at Community Health Centers are regarding Human Resource Limitations, what the responsibilities of Community Health Centers are in implementing the Referral Service System, as well as the impact of excessive performance burdens on Health Workers at Community Health Centers. The research method used is a normative juridical approach accompanied by library data collection. The results of this research were then analyzed qualitatively. Based on the research results, it shows that in principle the referral procedure at the Community Health Center regarding limited human resources is the same as the referral principle in general. Every health worker is still required to be multiskilling in providing health services at the Community Health Center. There must still be health workers accompanying patients in carrying out referrals. Puskesmas also has the authority to place competent health workers as companions if the patient's condition is not good. Workload is a combination of quantitative workload and qualitative workload. The impact of excessive performance burden by Health Workers is stress, fatigue, human error, and vulnerability to disease transmission.